Early Childhood Teacher Professionalism Based on Academic Qualifications and Work Experience - Syafrimen Syafril; Devi Kurniawati; Agus Jatmiko; Ida Fiteriani; Cahniyo Wijaya Kuswanto (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2021)
This study aims to analyze the professionalism of early childhood teachers in mastering the material based on academic qualifications and work experience. The approach to research sequential explanatory mixed methods design; The first phase using descriptive quantitative involving 57 teachers, data were collected through a questionnaire, analyzed descriptively and inferentially assisted by SPSS version 26.0. The second phase used a holistic multi-case study involving six school principals, data were collected through in-depth interviews and analysis documents, analyzed interactively with the assistance of Nvivo 12.0. The results showed that there was no difference in teacher professionalism based on academic qualifications and work experience. The second phase finds; teacher professionalism is not only influenced by academic qualifications and work experience, teacher professionalism is also influenced by various professional trainings that have been attended, and prospective teachers who choose the early childhood education programs major do not fully understand the substance of the lecture program related to their professionalism.